04 PROSPEK PENGEMBANGAN USAHA CEMILAN DAN KUE KERING (Studi Kasus Usaha Ibu Di Btn Solindo Kerjasama Program Coop Stiper Yapim Maros) - Jurnal Agribis; Riski Amalia; Zulkifli Zulkifli; Abd. Asis Pata (Jurnal Agribis, 2017)
This research was conducted in the Batangase area, Mandai District, Maros Regency. This location was chosen with the consideration that it has long been producing snacks and cookies made from peanuts. There are two data used, namely: Primary data, namely data obtained from observations through direct interviews and also through the help of questionnaire lists and secondary data, namely data obtained from agencies / institutions that are related or related to this research. The purpose of this study was to determine the Prospect of Snack and Pastry Business Development (Case Study of Mother's Business at Btn Solindo Cooperation, Coop Stiper Yapim Maros Program) in the future. The results of this research can be seen that the strengths and opportunities that are owned by the mother's business are higher than the weaknesses and threats that will be faced in the future and the business of snacks and pastries for the mother's business deserves to be maintained